Low flow frequency analysis on selected rivers in malaysia - Ni, Lar Win*; Khin, Maung Win* (Cafet Innova Technical Society, 2014)
Prediction of low flow of a river in magnitude as well as in frequency is necessary for the planning and design of water resource projects since low flow affects significantly in water supply, water quality and river ecological status. A number of probability distributions are used to estimate low flow discharges with various return periods of extreme hydrologic events. Among others, Gamma, Gumbel, Lognormal with 2 and 3 parameters, LogPearson Type III and Weibull distributions are used in this study. The objectives of this study are: (i) to carry out the low flow frequency analysis with the above mentioned probability distributions to selected rivers in Malaysia, (ii) to identify the most appropriate probability distribution for the basins under study and (iii) to determine the low flow for selected return periods. Frequency analysis is carried out using frequency factor method to determine annual minimum low flow. The two most commonly used tests of goodness of fit namely Chi-Square (CS) and Kolmogorov-Smirnov (KS) tests are applied to the data series to check the fit of probability distributions used in this study. Based on the analysis of statistical tests, Gamma, 2P and 3P Lognormal and Log-Pearson Type III distributions fit well to the Kelantan river. Gamma and Lognormal 3P distributions fit well to the Johor river. Lognormal 2P distribution is the best fit to the Muda river followed by Lognormal 3P distribution. In overall, 2P and 3P Lognormal distributions are recommended in estimation of low flow discharges for all the rivers under study which can be used in water quality and quantity management at gauged and ungagged sites.